2014
DOI: 10.1590/s0100-06832014000400015
|View full text |Cite
|
Sign up to set email alerts
|

Atributos químicos do solo associados à produtividade do trigo em um talhão com diferentes potenciais produtivos

Abstract: RESUMOPotenciais produtivos distintos têm sido verificados entre talhões, bem como dentro desses, em áreas sob muitos anos de plantio direto (PD). Ferramentas de agricultura de precisão (AP) podem auxiliar a identificar tais diferenças, mas para manejar eficientemente a fertilidade do solo nessas condições a amostragem deve ser representativa. Este trabalho teve como objetivo avaliar a influência de atributos químicos do solo, conforme a camada ou profundidade de amostragem, na produtividade da cultura do trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(13 reference statements)
1
2
0
3
Order By: Relevance
“…Excess rainfall in the winter of 2011 (Figure 1), associated to the greater nitrate levels from N fertilization, and to the greater repulsion of this anion by the soil colloids with liming, may be the cause of the greater Mg 2+ leaching in this treatment (Crusciol et al, 2011). The correlation between wheat grain yield and Mg 2+ levels was significant (r=0.53**) at 0-0.1 m soil depth, which corroborates the observations of Kramer et al (2014) of a positive correlation between wheat grain yields and Mg 2+ levels at 0-0.1 m soil depth. Caires et al (2015) reported linear decreases in Mg 2+ content at the soil surface with liming, and stipulated that increasing amounts of Mg 2+ leached below 0.6 m soil depth, in treatments with 4, 8, and 12 Mg ha -1 of lime, associated with 180 kg ha -1 N.…”
Section: Resultssupporting
confidence: 83%
“…Excess rainfall in the winter of 2011 (Figure 1), associated to the greater nitrate levels from N fertilization, and to the greater repulsion of this anion by the soil colloids with liming, may be the cause of the greater Mg 2+ leaching in this treatment (Crusciol et al, 2011). The correlation between wheat grain yield and Mg 2+ levels was significant (r=0.53**) at 0-0.1 m soil depth, which corroborates the observations of Kramer et al (2014) of a positive correlation between wheat grain yields and Mg 2+ levels at 0-0.1 m soil depth. Caires et al (2015) reported linear decreases in Mg 2+ content at the soil surface with liming, and stipulated that increasing amounts of Mg 2+ leached below 0.6 m soil depth, in treatments with 4, 8, and 12 Mg ha -1 of lime, associated with 180 kg ha -1 N.…”
Section: Resultssupporting
confidence: 83%
“…Since in Brazil and other South American countries NT is used uninterruptedly, there is no periodic soil tillage, the accumulation of crop residues in the topsoil and the addition of lime and fertilizers to the surface intensifies soil stratification over time, leading to the accumulation of organic C and N (Ebeling et al, 2008;Venzke Filho et al, 2008), as well as P, K + , Ca 2+ and Mg 2+ to depths of 0.0-0.10 m (Klein et al, 2007;Spera et al, 2011;Acqua et al, 2013;Kramer et al, 2014). Since the vertical mobility of lime is reduced in NT, the subsurface soil changes to a more acidic environment with higher concentrations of exchangeable aluminum (Al 3+ ) (Raij et al, 1998;Ernani et al, 2001), creating a chemical limitation to root growth.…”
Section: Introductionmentioning
confidence: 99%
“…Kramer et al (2014) also observed a correlation between wheat productivity and calcium and magnesium content in the soil.Productivity presented a negative correlation with sand and aluminum contents and a positive correlation with clay content, corroborating the results found by Rodrigues et al (2012) in a study conducted with corn under no-tillage system. The negative correlation between productivity and aluminum content shows that high aluminum contents decrease productivity.…”
mentioning
confidence: 68%